Cultura financiera y tributaria en estudiantes de las escuelas profesionales de Contabilidad y Negocios Internacionales – Unap, sede Iquitos – 2022 - Guerra Rios, Bryan (2023)
The present investigation covered the level of financial and tax culture, reached by the students of the professional schools of Accounting and International Business and Tourism of the UNAP, from the Iquitos headquarters, period 2022, having developed a descriptive – quantitative study – not experimental. The study population and the sample consisted of 122 students enrolled in the fifth level, using the survey technique and the questionnaire as an instrument. The level of financial education was identified, finding that the students of both schools have a medium level; therefore, the degree of knowledge acquired within their higher education was not as expected (high level), however, they develop consumption-oriented practices and savings habits, with a good administration of their resources and consider the importance of taking efficient and responsible financial decisions. Likewise, the level of tax education was identified, finding that university students have a medium level, therefore, although the results obtained are not the desired ones (high level); however, they demonstrated to have acceptable knowledge and good training, because they develop tax awareness practices, which are related to tax obligations, and also opt for making better decisions.